FROM ARCHIVES TO PUBLIC SPACE: ART ARCHIVING PRACTICES IN INDONESIA - Astuti, Ayu; Lawanda, Ike Iswary (UI Scholars Hub, 2026)
Art archives hold a crucial role in the production of knowledge and the writing of art history. In Indonesia, however, the management and accessibility of art archives remain uneven, resulting in significant gaps within art historiography. This article examines how art archives function not merely as repositories of documentation, but as cultural practices and public knowledge infrastructures that shape the conditions of art history writing. Using a qualitative approach, this study combines literature review with case studies of selected archival initiatives in Indonesia, including the Indonesian Visual Art Archive (IVAA), Pusat Dokumentasi Salihara, and Dicti Art Laboratory. The findings reveal that the limited availability and accessibility of art archives contribute directly to the fragility of Indonesian art historiography, while independent and community-based archival initiatives have played a vital role in addressing this gap by activating archives through exhibitions, educational programs, and research-based curatorial practices. The article further highlights how these initiatives reposition archives from private or institutional storage into the public sphere, enabling new forms of interpretation and engagement. A comparative reflection on archival practices in Singapore demonstrates how the institutional integration of archives can strengthen research, collection development, and public access simultaneously. This study argues that strengthening Indonesian art historiography requires not only new scholarly interpretations, but also sustained attention to archival practices, governance, and access. By situating art archives as active sites of knowledge production rather than passive historical traces, this article underscores their significance in shaping more inclusive and sustainable narratives of Indonesian art history.